2004
DOI: 10.1108/09544780410563301
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social reporting in Irish financial institutions

Abstract: This paper proposes a four-state framework for measuring corporate social responsibility reporting and argues that TQM or excellent organisations should be in an advanced state of social responsiveness, and that this should be reflected in their reporting of such activities. A study of six Irish financial institutions is used to demonstrate the extent of social reporting in company annual reports and Web sites with a view to positioning them on the framework. Social reporting in the annual reports is compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 14 publications
9
124
2
5
Order By: Relevance
“…Si bien, en el sector bancario, como apuntan Orozco, Martínez & Boton (2012), existen investigaciones que se han encargado de la divulgación de la información sobre RSC, estas se han limitado a estudiar un país o entorno en particular (Douglas, Doris & Johnson, 2004;Castelo & Lima, 2006;Vázquez & análisis de las memorias de sostenibilidad de la banca internacional Vol. 6, No.…”
Section: Introductionunclassified
“…Si bien, en el sector bancario, como apuntan Orozco, Martínez & Boton (2012), existen investigaciones que se han encargado de la divulgación de la información sobre RSC, estas se han limitado a estudiar un país o entorno en particular (Douglas, Doris & Johnson, 2004;Castelo & Lima, 2006;Vázquez & análisis de las memorias de sostenibilidad de la banca internacional Vol. 6, No.…”
Section: Introductionunclassified
“…Many researchers investigating existing records management practices (e.g. Chinyemba and Ngulube 2005;Ndibalema 2001) and corporate social responsibility and sustainability strategies (Brady 2005;Douglas, Doris and Johnson 2004) in business organisations used the survey methods for data collection and analysis. Their data collection techniques included interviews, observations, questionnaires and scenario modelling.…”
Section: Methodsmentioning
confidence: 99%
“…A study on social disclosures in the annual reports of six Irish and four international banks by Douglas et al (2004) found that the Irish banks reported less information than the international banks. The social issues reported provided no quantifiable information, mainly addressed shareholders' concern, ignored issues such as public complaints received, legal challenges and employee satisfaction were considered 'at a fairly superficial level' [Douglas et al, (2004), p.394].…”
Section: Literature Reviewmentioning
confidence: 99%